Legal consequences of train-induced structure borne noise and vibration in residential buildings - Vasheghani Mojtaba; Sadeghi Javad; Khajehdezfuly Amin (Noise Mapping, 2022)
The development of subways in cities has provided great comfort to the citizens, but it has brought adverse effects to the residents of the buildings adjacent to the subway lines. The main effects are Structure Borne Noise (SBN) and Structure Borne Vibration (SBV), which are identified as environmental challenges. In this research, the extent and seriousness of SBV and SBN annoyances to people were investigated. This is made in two steps; first a thorough field test was made to evaluate the level of train-induced noise and vibration; then, a comprehensive investigation was made on the level of people annoyance from train-induced vibration and noise, using results obtained from interviews and questionnaires. The results obtained indicate that health concerns, economic losses, building damages and social harms were the most important factors, which cause annoyance of the citizens. These annoyances caused citizens to take their complaints to judiciary system in the world. In the second part of this research, the effectiveness and sufficiency of the current laws and legislation to protect the citizen against SBV/SBN annoyance are evaluated. The results indicate that there are limitations in the current laws in regard to crime determination, criminal identification, estimation of damages to citizens, citizen rights regarding the annoyance caused by SBV/SBN. Also, there is a lack of legal awareness among the citizens who do not know how to get their legal rights. The results of this research showed that the judicial bodies should improve and extend the current laws and make more low-enforcement to protect people against the growing problem of SBV/SBN. Also, there is a need to make people more familiar with their civil rights in regard to SBN and SBV.